2022
DOI: 10.3390/seeds1020008
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Salt-Inhibited Germination and Seedling Growth of Kidney Bean by Seed Priming and Exogenous Application of Salicylic Acid (SA) and Hydrogen Peroxide (H2O2)

Abstract: Salinity is a dominant obstacle to the proper germination of seeds, growth of seedlings, and, consequently, the production of crops. The priming of seeds with different treating agents can efficiently impart salinity tolerance. Kidney bean is a nutritious and popular vegetable crop in the world. Literature shows that salt stress negatively disturbs the germination and growth of kidney beans. In the present research, we investigated the potentiality of salicylic acid (SA) and hydrogen peroxide (H2O2) as priming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This was might be due to the variation in crop species and the nature of the priming agents. Similar findings were also reported by Ambreen et al [19], and Tania et al [20]. According to numerous earlier research, the reduced water intake, cell membrane damage, decreased cellular respiration, and raised reactive oxygen species (ROS) levels were the main causes of the delayed and uneven germination of rice under cold stress [21].…”
Section: Fig 2 Effects Of Different Priming Agents On Photosynthetic ...supporting
confidence: 84%
“…This was might be due to the variation in crop species and the nature of the priming agents. Similar findings were also reported by Ambreen et al [19], and Tania et al [20]. According to numerous earlier research, the reduced water intake, cell membrane damage, decreased cellular respiration, and raised reactive oxygen species (ROS) levels were the main causes of the delayed and uneven germination of rice under cold stress [21].…”
Section: Fig 2 Effects Of Different Priming Agents On Photosynthetic ...supporting
confidence: 84%
“…Previous studies indicated that Kh application increased antioxidant activity in pepper plants under saline conditions [ 79 ]. The role of SA treatment in salinity resistance was reported in some previous studies [ 33 , 34 , 35 ]. Increasing GSH and AA contents in plants by SA application could enhance a mechanism to protect plants from the accumulation of ROS under stress conditions [ 80 ].…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, SA enhanced plant growth by maintaining the expected levels of indole acetic and gibberellic acid levels responsible for plant growth [ 52 ]. Additionally, previous studies indicated that SA application mitigates salinity and improves growth (plant fresh and dry weight) of some crops, such as kidney beans and cabbage [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 is a signal molecule involved in phytohormone metabolism, such as SA-mediated signaling pathways. The synergistic action of H 2 O 2 and SA was able to boost germination in maize seeds by promoting the antioxidant response and energy metabolism, particularly under chilling (Luo et al 2017) and in kidney beans subjected to salt stress (Tania et al 2022 ). A similar protective role of H 2 O 2 -mediated priming was highlighted in rice seeds and seedlings under drought stress in rice (Jira-Anunkul and Pattanagul 2020), as well as cauliflower seeds and seedlings challenged with salt stress (Ellouzi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%